Fracture Strength of CAD/CAM CROWNS after Enhancement of Occlusal Morphology. (2022) - Passos, L.; Butler, S.; Torrealba, Y.; Linke, B.
Abstract : Purpose/Aim: The aim of this study was to investigate the fracture strength of computer-aided design/computer-aided manufacturing (CAD/CAM) posterior ceramic crowns with and without post-milling manual enhancement of occlusal morphology (MEOM), as indicated especially with early CAD/ CAM restorations that have limited capacity to generate natural occlusal morphology. Materials and Methods: A mandibular molar of an acrylic tooth model was prepared to receive a CAD/CAM all-ceramic crown and was used as a master die to fabricate 80 prepared tooth replicas using an epoxy resin with an elastic modulus (E) of 18 GPa. The crown was designed using CEREC softwares Biogeneric Copy Design mode (Sirona). Eighty identical monolithic crowns were fabricated by milling four types of ceramic blocks. Forty monolithic crowns (10 of each ceramic system) were randomly selected as the control group, and MEOM was performed for each of the other 40 crowns by a certified dental technician. Restorations were crystallized and glazed according to the manufacturers instructions and firing protocols. All crowns were cemented to their respective die using resin cement and loaded to fracture at a crosshead speed of 0.5 mm/min. The resultant fractures were classified into three modes. Data were statistically analyzed using the nonparametric Mann-Whitney U test at ? = 0.05. Results: The MEOM treatment decreased the fracture load for all ceramic brands. Conclusions: The MEOM procedure should be considered detrimental for monolithic CAD/CAM-generated crowns and should thus be avoided.